Effects of Adding Different Corn Residue Components on Soil and Aggregate Organic Carbon - Ninghui Xie; Liangjie Sun; Tong Lu; Xi Zhang; Ning Duan; Wei Wang; Xiaolong Liang; Yuchuan Fan; Huiyu Liu (Agriculture)
Soil organic carbon (SOC) plays a vital role in maintaining soil fertility and ecosystem sustainability, with crop residues serving as a key carbon input. However, how different maize residue components influence SOC stabilization across aggregate sizes and fertility levels remains poorly understood. This study investigated the effects of maize roots, stems, and leaves on SOC dynamics and aggregate-associated carbon under low- and high-fertility Brown Earth soils through a 360-day laboratory incubation. Results revealed that residue incorporation induced an initial increase in SOC, followed by a gradual decline due to microbial mineralization, yet maintained net carbon retention. In low-fertility soil, leaf residues led to the highest SOC content (12.08 g kg−1), whereas root residues were most effective under high-fertility conditions (18.93 g kg−1). Residue addition enhanced macroaggregate (>0.25 mm) formation while reducing microaggregate fractions, with differential patterns of SOC distribution across aggregate sizes. SOC initially accumulated in 0.25–2 mm aggregates but gradually shifted to >2 mm and <0.053 mm fractions over time. Root residues favored stabilization in high-fertility soils via mineral association, while stem and leaf residues promoted aggregate-level carbon protection in low-fertility soils. These findings highlight the interactive roles of residue type and soil fertility in regulating SOC sequestration pathways.